Pengembangan Multimedia Interaktif Pembelajaran Membaca Teks Berhuruf Jawa untuk Siswa Kelas VII SMP di Kecamatan Ungaran Timur - Arum, Fajar; Sudi Utami, Esti; Kurniati, Endang (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Grade VII junior high in Ungaran Timur was bored with learning to read the text in a monotonous Java. This is due to gurus only use the textbook so that interest students in reading the text in Java is less. Therefore, the purpose of this research is to develop an interactive multimedia learning reading text in Java. The methods used in this research, namely research and development (R and D). The results of this research in the form of a prototype interactive multimedia learning reading text in Java. The prototype drew up based on the needs of students and teachers. The shape of the prototype in the form of interactive multimedia applications. Lettered text impressions of Java through a picture story and accompanying audio as a confirmation. The tested product design validation by expert media, material, and teachers as users. After the repair of the product design in accordance with the suggestions of the validator, interactive multimedia learning reading text in Java considered worthy to be used by students of Class VII junior high in Ungaran Timur.